Some problems of biotechnology for growing of larvae of giant freshwater prawn Macrobrachium rosenbergii (Decapoda: Palaemonidae) - Svetlana V. Statkevich (Известия ТИНРО)
Giant freshwater prawn Macrobrachium rosenbergii (De Man, 1879) is cultivated in Crimea since 2000 and technology of complete cycle of its cultivation from planting material to saleable product is successfully applied nowadays. This area is located beyond of the species native habitat and has other environments, so the larvae and juveniles can harvested in controlled conditions only: the open water bodies with the water temperature above 20оC are recommended. Growing of the larvae in artificial conditions is the most difficult stage of the biotechnological process, with high mortality because of diseases, grazing by planktophages, and poor water quality. These factors were studied in conditions of spawn farm in 2001-2013 and the main reasons of the prawn mortality at the larval stage were revealed. They were the gas-bubble disease, low oxygen content in tanks, and penetration of predatory hydromedusae Sarsia tubulosa to tanks. All these problems were caused by failures in the cultivation technology. Measures for prevention of the prawn larvae disease because of external factors are proposed.